PENERAPAN RANGE OF MOTION (ROM) TERHADAP KEKUATAN OTOT PASIEN STROKE DALAM PEMENUHAN KEBUTUHAN AKTIVITAS - Fitria - Hasanuddin; Rahmawati - Said; St. Suarniati - - (Media Keperawatan:Politeknik Kesehatan Makassar, 2019)
ABSTRACTThe most common cause of death in the world is among strokes. Where strokes rank third as the main cause of death after coronary heart disease and cancer in developing countries. Of the 56.4 million deaths worldwide in 2015, more than half (54%) were caused by 10 main causes, one of which was ischemic heart disease and stroke. In Indonesia, stroke ranks third in the cause of death, with an estimated 500,000 people affected by stroke. From this number there is a possibility that one third can recover, another third will experience mild to moderate functional disorders and the remaining third will experience severe functional disorders that require patients to carry out continuous bed rest and wrong actions to take are range of motion (ROM).This study aims to describe the application  range of motion (ROM) to muscle strength in stroke patients in meeting their activity needs. This study used a descriptive method with a case study approach in patients who had a stroke from July 10 to July 16, 2018. The instruments used were interview guidelines, wide patient documentation checklist. Data were analyzed based on the results of interviews, measurements of muscle strength and joint degrees before and after range of exercise (ROM).The results of this study after the morning and evening range of motion were found to increase muscle strength after Range Of Motion (ROM) exercise was performed on the 7th day and there was an increase in joint degrees in the limbs of the shoulders, elbows, thighs, and knees after Range training. Of Motion (ROM).The conclusion of this study is that giving range of motion is highly recommended for stroke patients in increasing muscle strength and improving the patient's condition.Keywords: Range Of Motion (ROM), Stroke